Was the Piraeus peninsula (Greece) a rocky island? Detection of pre-Holocene rocky relief with borehole data and resistivity tomography analysis - Pavlopoulos, Kosmas (2014)
According to historical documents, Piraeus was a rocky island consisting of the steep hill of Munichia, known as modern-day Kastella. It was connected to the mainland by a low-lying stretch of land ("Halipedon") that would flood with sea water most of the year and was used as a salt field whenever it dried up. Apart from being an area of archaeological interest, the extended area of "Halipedon" is densely populated, thus being of geotechnical interest and is currently being investigated through borehole and geophysical data analysis. 52 boreholes were lithologically-geomorphologically analyzed and results from 11 resistivity tomography profiles were considered. Lithostratigraphy of the borehole data was classified into three lithostratigraphic units: Cultural deposits, Pleistocene-Holocene deposits, pre-Holocene bedrock ("Marls of Piraeus"). The deeper unit shows a big depression in the southeastern part of the survey area and a circular sinking (channel) in its north part. These depressions were probably covered by the sea at a time when the southern part of the Piraeus peninsula was an island. This is confirmed by stratigraphical and geophysical investigation in the area where resistivity tomography profiles could be performed. The big southeastern depression is covered by the river sediments implying a high sedimentation rate. © 2013 Elsevier Ltd.